2004
DOI: 10.1177/172460080401900208
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cancer Chemotherapy in Relation to the Pretreatment Number of Lymphocytes in Patients with Metastatic Solid Tumors

Abstract: The evidence of lymphocytopenia has been demonstrated to predict a poor prognosis in terms of survival in advanced cancer patients. This finding is not surprising because of the fundamental role of lymphocytes in mediating tumor cell destruction. Despite the importance of lymphocytes in the pathogenesis of cancer, there are only few data about the profile and the function of lymphocytes during the various antitumor therapies, and in particular the relation between lymphocyte pretreatment number and response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 13 publications
6
79
1
Order By: Relevance
“…Host's immune response to cancer cells is in fact lymphocytedependent and different studies reported association between low or high lymphocyte count and survival. 34, 35 Interestingly, we found in the control group an advantage in term of PFS for patients who presented a high baseline lymphocyte count; Monocytes are attracted in tumor tissue by different chemokines, such as CCL-2 or CCL-5, produced by cancer cells, fibroblasts or immune cells. Once have reached the tumor site, these cells quickly differentiate into tumor-associated macrophages (TAMs).…”
Section: Patients' Characteristicsmentioning
confidence: 96%
“…Host's immune response to cancer cells is in fact lymphocytedependent and different studies reported association between low or high lymphocyte count and survival. 34, 35 Interestingly, we found in the control group an advantage in term of PFS for patients who presented a high baseline lymphocyte count; Monocytes are attracted in tumor tissue by different chemokines, such as CCL-2 or CCL-5, produced by cancer cells, fibroblasts or immune cells. Once have reached the tumor site, these cells quickly differentiate into tumor-associated macrophages (TAMs).…”
Section: Patients' Characteristicsmentioning
confidence: 96%
“…Specifically, pretreatment lymphopenia has been found to predict a poor response to chemotherapy in the setting of lung, breast and colorectal cancer (8). An elevated pretreatment PLR has been shown to predict poor outcome in the setting of SRS for early-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment markers of systemic inflammation, including an elevated platelet-to-lymphocyte ratio (PLR), elevated neutrophil count, low lymphocyte count and low serum albumin concentration, have been found to predict responses to anti-neoplastic therapies and disease outcomes across multiple different malignancies (5)(6)(7)(8)(9)(10)(11). However, these markers and the role the systemic immune system plays in treatment outcomes in the setting of SRS for brain metastases have yet to be fully evaluated.…”
mentioning
confidence: 99%
“…Similarly, pediatric ALL patients with an ALC at day 15 ≥ 350 cells/µL after induction chemotherapy experienced a 6-year overall survival of 87% [19]. [20]. In pediatric patients with Ewing sarcoma that achieved an ALC at day 15 after initial chemotherapy, treatment of ≥500 cells/µL had a 3-year overall survival of 68% compared with 32% for patients with an ALC < 500 cells/µL at day 15 after initial chemotherapy treatment [21,22].…”
Section: Absolute Lymphocyte Count and Chemotherapymentioning
confidence: 99%